Main research areas in kickboxing investigations: an analysis of the scientific articles of the Web of Science Core Collection - Leonid V. Podrigalo; Keo Shi; Olha O. Podrihalo; Olexandr A. Volodchenko; Olexandr I. Halashko (IP Iermakov S.S., 2022)
Background and Study Aim. Combat sports are among the most popular sports nowadays. Scientific support of combat sports is one of the urgent tasks of modern sports science. The purpose of this article is an analytical analysis of studies devoted to kickboxing. Material and methods. The bibliometric database Web of Science Core Collection (WoS) is analyzed. 194 articles that met the search criteria were selected for the primary analysis. We used bibliometric methods for processing the information received in the context of kickboxing. The VOSviewer 1.6.18 software was used: keyword analysis method and direct citation analysis with the construction of bibliometric maps, visualization of cluster density, and citation weights. Results. The constructed bibliometric maps made it possible to identify the leading thematic areas of research, the most popular areas of research in this area. They can be divided into sports and rehabilitation and recreational areas. In a sports context, these include the performance of technical and tactical elements of kickboxing, the study of the physiological characteristics of combat sports athletes; assessment of the main physical qualities and analysis of the adaptive potential of athletes; the study of biochemical and features of homeostasis, the state of the cardiorespiratory system; highlighting factors important for winning competitions. In the rehabilitation context, kickboxing is used to optimize the functional state, recover from injuries, and improve the quality of life of patients with chronic diseases. The use of the VOSviewer software, version 1.6.18, made it possible to conduct a comprehensive analysis of the problem, to determine the priority scientific directions in this area. In sports, this is an analysis of the technical and tactical indicators of athletes, the time spent on their implementation, the study of the metabolic characteristics of combat sports athletes, and the assessment of their physical qualities. Conclusions. The conducted bibliometric analysis of publications on the problem of kickboxing confirms the relevance of this area of sports science. There is a lack of research on a comprehensive study of success, monitoring the state of kickboxing athletes. These directions should be recognized as the most relevant in this area.